Language Contact Issues in Central Europe - Kontra, Miklós (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2011)
The paper will review some of the fundamental issues related to language con- tact in Central Europe both from a structural point of view and from the socio-political and historical point of view. Various language contacts, the language rights issues, both national and international, and the linguistic-human-rights-in-education of minorities will be discussed in some detail. It will be shown that most if not all nation-states in the re- gion pursue minority policies that are just about tolerated by the international community. Violations of Linguistic Human Rights in Hungary and other states will be discussed. The impact of the English-Only movement in the USA on Slovak language policy will be dem- onstrated. Finally, the European Union’s language policy will be examined in relation to what impact it may have on the language strife in the region.
Abstrakt (Kontakty językowe w Europie Środkowej. Wybrane zagadnienia). Artykuł stanowi przegląd najważniejszych zagadnień związanych z kontaktami językowymi w Eu- ropie Środkowej ze strukturalnego oraz społeczno-politycznego i historycznego punktu widzenia. Omówiono różne w swej naturze kontakty językowe, problemy praw języko- wych na poziomie krajowym i międzynarodowym oraz miejsce językowych praw czło- wieka w edukacji mniejszości (językowych i narodowych). Autor udowadnia, że polityka większości państw regionu wobec mniejszości jest trudna do zaakceptowania przez spo- łeczność międzynarodową. Przywołane zostaną przykłady naruszenia językowych praw człowieka na Węgrzech i w innych krajach. Omówiony będzie również wpływ amerykań- skiego ruchu English-Only na słowacką politykę językową, a także polityka językowa UE i jej rola w kontekście konfliktów językowych w regionie.
Keywords: language rights; language contacts; Central Europe; language policy; polityka językowa; Hungary